Supplier development, integration and procurement performance of steel manufacturing firms in Kenya - Kevin Gudda; Pauline Jeruto Keitany; Maurice Ombok (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study examined how supplier integration moderates the relationship between supplier development and procurement performance in steel manufacturing firms within Nairobi City County, Kenya. Research methodology: A mixed method research design and positivism approach were adopted for this study. A census with a population of 360 employees within the 10 steel firms in Nairobi City County, Kenya was conducted. Primary data was collected using questionnaires. The collected data was analyzed using SPSS V.26.0 and SmartPLS 4.0 programs to test for both direct and joint effects of the variables. Results: The results of the study revealed that supplier selection (?=0.50, t=8.309, p<0.05), supplier partnership (?=0.136, t=2.872, p<0.05), and supplier evaluation (?=0.127, t=2.884, p<0.05) have a positive and significant impact on the procurement performance. On the other hand supplier training (?= -0.086, t=1.683, p>0.05) had an insignificant effect on procurement performance. The study findings also show that supplier integration had significant negative effects on supplier partnership (?= -0.497, t=10.702, p<0.05), supplier evaluation (?= -0.097, t=2.323, p<0.05) and supplier training (?=0.264, t=4.988, p<0.05). However, the results indicate that supplier integration has no significant impact on supplier selection (?= -0.079, t=1.108, p>0.05). The indirect effect analysis showed that supplier integration (?= -0.142, t=1.108, p<0.05) has a negative and significant impact on procurement performance. Contributions: Steel manufacturing firms need to emphasize the significance of supplier selection, efficient communication and collaboration with suppliers, and continuous performance monitoring and risk management to improve procurement performance. These factors enhance the reliability, quality, and cost-effectiveness of their procurement operations, resulting in better outcomes and a competitive advantage in their respective markets.